Pengaruh Penambahan Prebiotik Inulin dari Bengkoang (Pachyrhizus erosus) terhadap Organoleptik Sinbiotik Set Yoghurt - Fatimah Jora; Minda Azhar; Edi Nasra (Jurnal Periodic Jurusan Kimia UNP, 2021)
Improving the quality of yoghurt can be done by adding prebiotics, known as yoghurt synbiotic sets. This study aims to determinine the effect of adding prebiotic inulin from bengkoang (Pachyrhizus erosus) to the synbiotic organoleptic of yoghurt sets. This research is an experimental research. The yoghurt synbiotic set was made with inulin concentration variations of 0.1%,0.3%,0.5% with an incubation time of 20 hours at 37˚C. Organoleptic data were processed statistically using the Wilcoxon test with a significance level of α=0.05%. Organoleptic test results showed that the addition of 0.3% inulin concentration did not have a significant effect on the sour aroma, white color and solid texture of the yoghurt set compared to without the addition of inulin. The results of wilcoxon analysis at α=0.05 on organoleptic test showed that there was no significant difference in the color, aroma and texture of the yoghurt set.